Evaluation of formalin in salted fish in the main market of Lambaro and Ketapang Aceh Besar - Twentyna Dolorosa Maretty; Fauzan Lubis Ahmad; Pahala Sitanggang Lucien; Faidillah Fitra; Julia Mizulni Putri (BIO Web of Conferences)
Salted fish is one of the favorite local fisheries processed foods by the Indonesian people, where the product is made through a preservation process using salt. The addition of prohibited preservatives such as formalin is still found, this is thought to be due to a lack of knowledge from artisanal fishers about salted fish processing that is safe for consumption. This research aims to determine the formalin content of salted fish in Lambaro Main Market and Ketapang and the distribution pattern of salted fish sales in the Aceh Besar Market. The formalin test was conducted qualitatively using a formalin kit with two repetitions. Data analysis was conducted descriptively. The results showed that three samples were positive for formalin at 38% in Lambaro Main Market (1st and 2nd repetition). While in Ketapang Market, there were two and three formalin positive samples (1st and 2nd repetition) at 29% and 43%, respectively. The distribution pattern of salted fish sales in Aceh Besar Market is very short, namely producers sell to collectors, then to traders in Lambaro and Ketapang Market, and forwarder to consumers. The salted fish producers come from Medan (North Sumatra), Meulaboh (West Aceh) and Blang Pidie (Southwest Aceh).